Prevalence of alveolar bone loss in healthy children treated at private pediatric dentistry clinics - Maria do Carmo Machado Guimarães; Valéria Martins de Araújo; Márcia Raquel Avena; Daniel Rocha da Silva Duarte; Francisco Valter Freitas (University of São Paulo, 2010)
OBJECTIVES: The purpose of this study was to evaluate the prevalence of alveolar bone loss (BL) in healthy children treated at private pediatric dentistry clinics in Brasília, Brazil. MATERIAL AND METHODS: The research included 7,436 sites present in 885 radiographs from 450 children. The BL prevalence was estimated by measuring the distance from the cementoenamel junction (CEJ) to alveolar bone crest (ABC). Data were divided in groups: (I) No BL: distance from CEJ to ABC is <2 mm; (II) questionable BL (QBL): distance from CEJ to ABC is >2 and <3 mm; (III) definite BL (DBL): distance from CEJ to ABC >3 mm. Data were treated by the chi-square nonparametric test and Fisher's exact test (p<0.05). RESULTS: Among males, 89.31% were classified in group I, 9.82% were classified in group II and 0.85% in group III. Among females, 93.05%, 6.48% and 0.46% patients were classified in Group I, II and III, respectively. The differences between genders were not statistically significant (Chi-square test, p = 0.375). Group composition according to patients' age showed that 91.11% of individuals were classified as group I, 8.22% in group II and 0.67% in group III. The differences among the age ranges were not statistically significant (Chi-square test, p = 0.418). The mesial and distal sites showed a higher prevalence of BL in the jaw, QBL (89.80%) and DBL (79.40%), and no significant difference was observed in the distribution of QBL (Fisher's exact test p = 0.311) and DBL (Fisher's exact test p = 0.672) in the dental arches. The distal sites exhibited higher prevalence of both QBL (77.56%) and DBL (58.82%). CONCLUSIONS: The periodontal status of children should never be underestimated because BL occurs even in healthy populations, although in a lower frequency.